2020
DOI: 10.4274/balkanmedj.galenos.2020.2020.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Risk Factors of Coronary Artery Lesions before Treatment Among Patients with Kawasaki Disease

Abstract: Background: Many children with Kawasaki disease develop coronary artery lesions before intravenous immunoglobulin treatment. However, little data are available on the prognosis of children with Kawasaki disease who developed coronary artery lesions before intravenous immunoglobulin treatment. Aims: To explore the outcomes of coronary artery lesions before intravenous immunoglobulin treatment in children with Kawasaki disease and analyze the factors that influence the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Coronary artery injury is mainly attributed to KD, accompanied by thrombosis and distal embolism, for which ASA, an antithrombotic drug, shows some certain preventive effect [ 19 ]. Finally, we confirmed through univariate and multivariate logistic regression analyses that gender, onset-to-treatment time, overweight, PLT, and treatment methods were independent risk factors for poor short-term prognosis of children with KD, similar to the results of Qiu et al [ 20 ]. The report of Huang et al [ 21 ] confirmed that PLT, CRP, neutrophil percentage, serum albumin, serum sodium, etc.…”
Section: Discussionsupporting
confidence: 89%
“…Coronary artery injury is mainly attributed to KD, accompanied by thrombosis and distal embolism, for which ASA, an antithrombotic drug, shows some certain preventive effect [ 19 ]. Finally, we confirmed through univariate and multivariate logistic regression analyses that gender, onset-to-treatment time, overweight, PLT, and treatment methods were independent risk factors for poor short-term prognosis of children with KD, similar to the results of Qiu et al [ 20 ]. The report of Huang et al [ 21 ] confirmed that PLT, CRP, neutrophil percentage, serum albumin, serum sodium, etc.…”
Section: Discussionsupporting
confidence: 89%
“…Due to lack of height data, no mean body surface area (BSA)-adjusted Z-score was available. CALs were defined according to an internal lumen diameter of > 2.5 mm in patients < 3 years of age, > 3 mm in patients aged 3–9 years, and > 3.5 mm in patients aged 9–14 years; an internal segment diameter ≥ 1.5 times that of an adjacent segment; and an irregular lumen [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Kobayashi system was invalid in identifying CALs in our Chinese cohort with the AUC below 0.5. Notably, previous studies reported that the infusion of IVIG after 10 days of the illness course was an independent risk factor for CALs ( 43 , 44 ), yet our corresponsive data was 6 days. The reasons might be due to renewal of the diagnostic criteria and the suggestion of IVIG infusion as soon as the diagnosis can be established ( 1 ).…”
Section: Discussionmentioning
confidence: 54%